Critical thinking skills student profile and PBL needs assisted by android physics module - Tsabitah Farah Dina; Binar Kurnia Prahani; Marianus Marianus; Firmanul Catur Wibowo; Lari Andres Sanjaya (Momentum: Physics Education Journal, 2024)
The research was conducted to analyze the level of students critical thinking skills and and the requirements for implementing PBL using android modules to improve students critical thinking skills in physics. This research method was included in the preliminary research with a sample of 174 students in XI grade MIPA at Gresik State High School. Data collection is done by sharing critical thinking tests with students, conducting questionnaires for students, and conducting teacher interviews. The data is examined both qualitatively and descriptively to explain the research's findings. The results of this research showed that 1) many students still had a low level of critical thinking. Of the 174 students, 119 have low level, 44 have medium level, and 10 have high level. The evaluation indicator has the lowest average value, and the interpretation indicator has the highest average. Student critical thinking skills are higher for females than for males. The conclusion is that the skills to think critically is very important during learning, especially in physics. To improve the critical thinking skills of students, the way that can be done is by applying PBL-assisted android modules.